2017
DOI: 10.1175/jhm-d-16-0218.1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Precipitation in the West African Cities of Dakar and Ouagadougou: Atmospheric Dynamics and Implications for Flood Risk Assessments

Abstract: Two extreme, high-impact events of heavy rainfall and severe floods in West African urban areas (Ouagadougou on 1 September 2009 and Dakar on 26 August 2012) are investigated with respect to their atmospheric causes and statistical return periods. In terms of the synoptic–convective dynamics, the Ouagadougou case is truly extraordinary. A succession of two slow-moving African easterly waves (AEWs) caused record-breaking values of tropospheric moisture. The second AEW, one of the strongest in recent decades, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 64 publications
(65 reference statements)
3
51
0
Order By: Relevance
“…In West Africa, more than 75% of studies were from Senegal (figure 1(a)). One possible reason why Senegal has been the focus of more studies relates to the international attention and media coverage elicited by historic climate and weather related disasters in the Sahel region, including droughts in the 1970s and 1980s and flooding in the 2000s (Tschakert et al 2010, Engel et al 2017. Our literature search also showed that studies of users' needs for climate services are more numerous for the agriculture and food security sector than the other focal sectors, with more than 50% of studies satisfying the inclusion criteria for this review focusing on agriculture or food security ( figure 1(b)).…”
Section: Resultsmentioning
confidence: 99%
“…In West Africa, more than 75% of studies were from Senegal (figure 1(a)). One possible reason why Senegal has been the focus of more studies relates to the international attention and media coverage elicited by historic climate and weather related disasters in the Sahel region, including droughts in the 1970s and 1980s and flooding in the 2000s (Tschakert et al 2010, Engel et al 2017. Our literature search also showed that studies of users' needs for climate services are more numerous for the agriculture and food security sector than the other focal sectors, with more than 50% of studies satisfying the inclusion criteria for this review focusing on agriculture or food security ( figure 1(b)).…”
Section: Resultsmentioning
confidence: 99%
“…We use moderate rain spells (≃20–100 mm of accumulated rainfall in less than 7 days consecutive wet days—with isolated dry days allowed) not followed by a 10‐day (or longer) dry spell. Moderate rain + dry spell (April to July). It is also a moderate rain spell (see above) but which is followed by a dry spell of at least 10 days. The number of intense days (>30 mm/day) (July to September) is important for agriculture, as it can enhance soil erosion and nutrient leaching. Short and intense (July to September) subdaily rainfall can lead to flash floods with devastating effects (Engel et al, ). We provide the number of wet spells lasting 9 hr or less and accumulating more than 75 mm of rainfall. Long and intense wet spells (July to September) last at least 7 days with high cumulative rainfall (>100 mm).…”
Section: Resultsmentioning
confidence: 99%
“…Note that several other studies, especially in regions showing a low density of stations, similarly carried out a direct comparison between rain-gauges and the nearest grid-point (e.g. Buarque et al, 2011;Scheel et al, 2011;Maussion et al, 2014;Engel et al, 2017;Wehbe et al, 2017). Engel et al (2017) also investigated the impact of increasing numbers of stations in grid cells of varying size.…”
Section: Methodsmentioning
confidence: 99%